Phylogeography of two hybridizing southern beeches (Nothofagus spp.) with different adaptive abilities - Soliani, Carolina; Gallo, Leonardo Ariel; Marchelli, Paula (Tree Genetics & Genomes, 2011)
In phylogenetically related plant species, hybridization can influence their current genetic structure. Long-lasting hybridization may be related to persistence in shared glacial refugia, where the differential abilities of each species to survive could have provided adaptations to changing environmental conditions. In temperate South American forests at the Patagonia region, the pattern of Quaternary glaciations offered several opportunities for refuge. At mid-latitudes (42° to 44° S), particular topographic characteristics determined different glaciation patterns, defining the existence of a transitional zone. We studied two widespread Nothofagus species (Nothofagus pumilio, Nothofagus antarctica) characterized by contrasting plasticity. We screened 40 coupled populations with three cpDNA markers and found 14 different haplotypes. Both species presented significant phylogeographic structure (N ST ≥ G ST, p > 0.001), with two geographically segregated lineages (north–south). A latitudinal cline in the distribution of genetic diversity was determined, with most variable populations in the north (35°–41° S). Population diversity diminished to southern latitudes, but a particular situation occurs between 42°S and 44°S. The transition zone, a putative refuge area, presented unique haplotypes. The more plastic species, N. antarctica, probably persisted in more refuge areas, which could be reflected in its higher levels of diversity. In these species, sympatric distribution explains introgression (IG > IG e), but the differential levels of haplotype sharing between N. pumilio and N. antarctica at population level are relevant to the understanding of phylogeographic patterns. Hybridization may have facilitated recruitment in the onset of postglacial colonization by middle to long-distance pollen dispersal. In the current scenario of climate change, the presence of hybrids with different plastic responses is of remarkable importance. EEA Bariloche Fil: Soliani, Carolina. Instituto Nacional de Tecnología ...